Evaluasi Pelaksanaan Program Rehabilitasi Rumah Tidak Layak Huni: Studi Kasus di Kelurahan Kolo Kecamatan Asakota Kota Bima - Hendra Hendra; Muhammad Nur Rijal; Nike Ardiansyah; Firliah Rizkiani; Faujan Faujan (BADAN PENERBIT STIEPARI PRESS, 2025)
The problem of uninhabitable houses (RTLH) is still a strategic issue in settlement development in Indonesia, including in Bima City. This study aims to evaluate the mechanism for receiving assistance and the criteria for environmental infrastructure in the implementation of the RTLH social rehabilitation programme in Kolo Village, Asakota Sub-district, Bima City. The method used was descriptive qualitative with data collection techniques through in-depth interviews with key informants, such as kelurahan officials, programme assistants, and beneficiary communities. The results showed that the implementation of the RTLH program fulfilled the six main indicators of the mechanism for receiving assistance, including legal identity ownership, economic inability, dependence on food assistance, ownership of inadequate housing, and legal land ownership. In addition, five indicators of environmental facilities and infrastructure criteria were also considered very suitable, such as location suitability, legality, community needs, and community participation. In conclusion, the RTLH programme in Kelurahan Kolo is effective and well-targeted, in terms of administrative, social, and participatory aspects. The findings are expected to be an input for the development of housing policies that are more responsive to the needs of low-income communities.